Response of basmati rice varieties to integrated nutrient management. (7th February 2021) - Sravan, Uppu Sai; Singh, Shiv Prakash; Neupane, Madhav Prasad
Abstract: Yield performance of Basmati varieties bred for unconventional areas were assessed under integrated nutrient management. A two-year study conducted in split plot design involving two varieties and three fertility levels in main plots and three bio-inoculants to sub plots. Variety HUBR 10-9 exhibited increased mean yield (18.8%) and nitrogen use efficiency (NUE) over HUBR 2-1. Integration of 75% recommended dose of NPK fertilizers (RDF) with 25% recommended dose of nitrogen (RDN) applied as farmyard manure (FYM) registered highest yield and NUE. Combined application of blue green algae (BGA) and Azospirillum improved yields and NUE than their alone application. Findings suggest that HUBR 10-9 be grown with integration of 75% RDF, 25% RDN as FYM along with BGA and Azospirillum to enhance growth, yield, and NUE. More studies required in potential areas under diverse conditions.